PMO-065 Repair of fractured central venous catheters for parenteral nutrition: techniques and risk of infection. (28th May 2012) - Small, M; Major, G A D; Gabe, S M
Abstract : Introduction: Tunnelled central venous catheters (CVCs) are the best method of vascular access for long-term parenteral nutrition. Failure of intravenous access can necessitate emergeny admission. Removing and replacing CVCs is painful, risks infection and venous thrombosis, and uses costly healthcare resources. Simple techniques to repair fractures in the external part of CVCs can prolong CVC life but repairs have been associated with increased rates of catheter-related bloodstream infection (CRBSI). Methods: Between January 2010 and December 2011 all repairs of CVC fractures were recorded. Fractures were defined as "external" when only the outer sheath of the CVC was ruptured, and "full" when both inner and outer sheaths of the CVC were ruptured, with evidence of leakage. External fractures were repaired with waterproof, non-absorbent tape. Full fractures were repaired with the manufacturer's repair kit, including a metal spike inserted into the lumen across the new join. We recorded rates of successful repair and any instance of CRBSI within 30 days of the repair. Results: Conclusion: CVC fracture repair is effective and safe. Repair of external fracture is easily done with waterproof, non-absorbable tape. Formal repair can prevent emergency admission and act a bridge to planned CVC replacement. It may also have a role in further prolonging the useful life of tunnelled CVCs. In our patient cohort repair is not associated with subsequent infection. Competing interests: None declared. Reference: 1. Lundgren IS, Zhou C, Malone FR, et al. Central venous catheter repair is associated with an increased risk of bacteremia and central line associated bloodstream infection in pediatric patients. Pediatr Infect Dis J, 2011.